Influence of Boycott, Price, and Product Quality on Consumer Decisions for Unilever Sanitation Product in Pontianak - Lestari Lestari; Nur Aini Anisa; Komarun Zaman (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2025)
This study aims to examine the extent to which boycott actions, price, and product quality influence consumer purchase decisions regarding Unilever’s sanitation products in Pontianak. A quantitative approach was employed, and data were collected using questionnaires distributed to 100 respondents selected through purposive sampling. The data were analyzed using multiple linear regression, t-tests, and F-tests. The findings indicate that both consumer boycott and price do not have a significant impact on purchase decisions. In contrast, product quality has a positive and statistically significant effect (β = 0.382; sig. = 0.029). The constant value of 33.611 suggests that even when all independent variables are assumed to have no effect, the purchase decision level remains high. The R square value of 0.072 indicates that the three variables together explain only 7.2% of the variance in purchase decisions. The F-test result of 1.856 with a significance level above 0.05 confirms that the independent variables do not have a simultaneous effect. These findings highlight that product quality remains the dominant factor influencing purchase decisions, even amid social issues such as boycott movements.